Establishing the First Diagnosis of Follicular Thyroid Carcinoma from the Femoral Metastatic Site in an 84-year-old Woman - Liu, MD, PhD, Yunguang; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2013)
Follicular thyroid carcinoma (FTC) commonly presents as a solitary thyroid nodule, which is diagnosed by thorough examination of thyroidectomy/lobectomy specimen for capsular and vascular invasions. First diagnosis of FTC from femoral metastasis is very rare. Here, we report such a case in an 84-year-old woman who presented with increasing pain in her left thigh. A bone scan revealed multiple lesions in the bones including left femur. Four years ago, the patient suffered right humeral pathological fracture. The humeral lesion was positive for TTF-1 and was interpreted as “metastatic non-small cell carcinoma consistent with lung primary”. However, subsequent bronchial washing and lung biopsy were negative for malignancy. Biopsy of left femoral lesion showed solid nests of cells with round to oval nuclei and abundant eosionophilic/granular cytoplasm. The nuclei of tumor cells contain one or more nucleoli and granular/vesicular chromatin. No typical nuclear morphology of papillary thyroid carcinoma (PTC) was noted. The tumor cells are positive for thyroglobulin and TTF-1, consistent with metastatic tumor from thyroid primary. Immunostains of HBME-1 and CK19 only mark scattered tumor cells, which do not support the differential diagnosis of metastatic PTC. CD56 and CK7 stains are both positive. Upon further communication, patient's remote history of “thyroid follicular adenoma”, status post right lobectomy was obtained. The femoral lesion was negative for BRAF mutation. In conclusion, based on the overall morphological and immunohistochemical features as well as patient’s history, the final diagnosis of metastatic FTC was made. We would like to raise the awareness that metastatic FTC should be included in the differential diagnoses for tumors metastasized to bone to avoid misdiagnosis.